Measures of Bone Morphology in the Medial and Lateral Condyles of the Metacarpus in Beef Cross Dairy Cattle at 8–12 and 24 Months of Age - Gibson MJ; Hickson RE; Dittmer KE; Back PJ; Rogers CW (MDPI (Basel, Switzerland), 2022)
Bone morphology in the mid-diaphysis of the metacarpus in cattle and the effect of puberty and age has been well described. However, there is limited information on how age and not attaining puberty affects bone morphology in the epiphysis of the metacarpus. The metacarpus is comprised of the third and fourth metacarpal bones fused together to create a medial and lateral epiphysis. When a cow is in stance phase there is greater pressure on the medial claw; however, the effect of this difference in loading on bone has not been described. Therefore, the aim of this experiment was to describe bone morphology in the medial and lateral epiphysis of the metacarpus at the age of puberty in steers. The metacarpus was collected from beef cross dairy steers at approximately one and two years of age. The distal epiphysis of the metacarpus was scanned using peripheral quantitative computed tomography (pQCT). Measures were corrected for body weight and demonstrated a lack of bone growth cessation at one year of age. The lack of difference in bone morphology in the medial and lateral condyles of the distal metacarpus reflects the even loading distribution observed in the forelimb of cattle.
Keywords: epiphysis; metacarpus; puberty; bone strength; pQCT